The house of lost horizons : a Sarah Jewell mystery - Mignola, Mike; Mignola, Mike; Roberson, Chris (Dark Horse Books, 2022)
"A locked-room murder mystery puzzles paranormal detective Sarah Jewell and her associate Marie Therése when a weekend trip on a private island off the coast of Washington goes awry. Trapped by a storm and surrounded by myriad suspects who have gathered for an auction of occult items, the intrepid duo must unravel the supernatural mysteries surrounding the guests in the hopes of uncovering the murderer! But all the while bodies keep piling up, and at any moment Sarah or Marie Therése could be next!"--